Detection of Borrelia burgdorferi in urine of Peromyscus leucopus by inhibition enzyme-linked immunosorbent assay. - Magnarelli, L A (1994)
An inhibition enzyme-linked immunosorbent assay was developed to detect Borrelia burgdorferi, the etiologic agent of Lyme borreliosis, in urine from white-footed mice (Peromyscus leucopus). Of the 87 urine specimens tested from 87 mice collected in widely separated tick-infested sites in Connecticut, 57 (65.5%) contained detectable concentrations of spirochetal antigens. Forty-seven (62.7%) of 75 serum samples analyzed contained antibodies to B. burgdorferi. In culture work with tissues from bladders, kidneys, spleens, or ears, 50 of 87 mice (57.5%) were infected with B. burgdorferi. Thirty-eight (76%) of 50 infected mice had antigens of this spirochete in urine, while 36 (72%) individuals had infected bladders. Of those with infected bladders, 24 (66.7%) mice excreted subunits or whole cells of B. burgdorferi into urine. Successful culturing of B. burgdorferi from mouse tissues, the presence of serum antibodies to this bacterium, and detection of antigens to this spirochete in urine provide further evidence that multiple assays can be performed to verify the presence of B. burgdorferi in P. leucopus.